ENHANCING PRE-SERVICE SPECIAL EDUCATION TEACHERS’ PEDAGOGICAL COMPETENCE IN TEACHING READING COMPREHENSION TO HEARING-IMPAIRED ELEMENTARY STUDENTS THROUGH FOTONOVELA MEDIA - Sri Rizqi Widasari; Rohmah Ageng Mursita; Murni Winarsih; Totok Bintoro; Asep Supena; Septiyani Endang Yunitasari (Universitas Muhammadiyah Makassar, 2026)
Reading comprehension is a fundamental literacy skill that is essential for deaf or hard-of-hearing students to access academic information and participate in social life. However, limited auditory input and language development challenges often create barriers to understanding written texts. This study aimed to enhance the pedagogical competence of pre-service special education teachers in teaching reading comprehension to hearing-impaired students through the use of fotonovela media. The study employed a quasi-experimental design using a pretest–posttest non-equivalent control group approach and was conducted at SLB Pangudi Luhur and SLB Santi Rama as authentic learning contexts. The participants were pre-service special education teachers divided into experimental and control groups. The intervention involved training and teaching practice using fotonovela media integrating visual supports, the Indonesian Sign System (SIBI), and principles of the Maternal Reflective Method (MMR). Pretest results indicated that the initial competence levels of both groups were relatively equivalent, while posttest results showed a significant improvement in the experimental group. The use of fotonovela media significantly improved the pedagogical competence of pre-service teachers, particularly in instructional planning, visual strategies, language and communication support, adaptive teaching practices, and student engagement. The improvement in teacher competence contributed to the development of students’ reading comprehension skills, including vocabulary understanding, identifying main ideas, sequencing events, recognizing story elements, answering questions, making simple inferences, and summarizing texts. These findings indicate that fotonovela media is an innovative and sustainable approach to strengthening teachers’ pedagogical competence while supporting literacy development among deaf students.